(untitled) (Revista de Investigaciones Universidad del Quindío, 2009)
The Escuelas Normales Superiores (Normal Superior Schools), accredited institutions to provide initial training of teachers of Preschool and Basic Elementary school, are on duty to accept a challenge of importance and quality; in this sense, the pedagogical practice is the essence that gives life and promotes a style in teachers’ performance, generally involved in their educational task. This research is a qualitative study, from an ethnographic-critical approach, which consisted on reviewing the pedagogic practices of students from the Normal Superior School in the communities in which the process of educational care for vulnerable populations in society is being developed; in order to discover what this experience actually means, and to refine the educational profile of students in their practices, while building their sense of being a teacher in the present historical, political and social circumstances of the region. This project also inquired the learning process of teachers in initial training, with childhood, adolescence, youth, family and community, potential beneficiaries of the Inclusive School Project, with the aim of understanding the pedagogical relations in community settings, under the framework of educational and social inclusion, as an emerging practice, based on the needs identified in these populations served by the trainer institution in its social outreach program.